GLOBALIZATION AND GLOBAL SECURITY (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
The concept of "global security" is a fundamental category in the theory of international relations and foreign policy practice. In the face of constantly changing asymmetric risks and threats to the national security of countries, the need to create a collective security system is growing. National security is directly related to international or more precisely global security. Above all, the global security environment is characterized by a rise in non-state and international threats to national security. This article examines the goals, objectives and elements of  globalization and global security.  The study argues that there cannot be a global security system in which there are no risks and threats to the international community, states and individuals.